SEA-FLOOR SPREADING IN MARGINAL BASINS OF WESTERN PACIFIC - Watts, A; Weissel, J; Larson, R (1977)
Observed magnetic lineations from the Shikoku, South Fiji, and West Philippine marginal basins are used to determine aspects of the tectonic evolution of these basins. In the western part of the Shikoku basin, anomalies 7 through 5E (~ 27-19 m.y. B.P.) are identified between the base of the Palau-Kyushu ridge and the center of the basin. In the eastern part of the South Fiji basin, anomalies 12 through 8 (~ 35-29 m.y. B.P.) are identified between the base of the Lau-olville ridge and the center of the basin. In the West Philippine basin, magnetic lineations which trend ESE-WNW have been mapped north of the Central Basin Fault. These lineations and the previously mapped lineations south of the fault (Louden, 1976) may be one limb of a Mesozoic spreading system, but more probably represent a two-limb system of Early Tertiary age. © 1977.